A Flexible Porous MOF Exhibiting Reversible Breathing Behavior through Single‐Crystal to Single‐Crystal Transformation. Issue 1 (9th January 2017) - Wang, Lin; He, Wei‐Wei; Yao, Zhao‐Quan; Hu, Tong‐Liang
Abstract: A two dimensional (2D) flexible Zn(II) MOF (1) with intra‐layer channels has been synthesized using a mixed ligand strategy. Interestingly, 1 exhibits reversible breathing behavior upon desolvation/resolvation in crystal state, causing responsive luminescence together with visible color changes. Furthermore, the above‐mentioned process even occurred when 1 exposed to humid atmosphere or immersed in various organic solvents. Abstract : A two dimentional flexible Zn(II) MOF with intra‐layer channels has been synthesized using a mixed ligands strategy. Interestingly, the MOF undergoes reversible SC‐SC transformation upon desolvation/resolvation, causing responsive luminescence with visible color change. Moreover, the reversible breathing behavior even occurred when this MOF exposed to humid atmosphere or immersed in various organic solvents.